Information technology governance and service management frameworks and adaptations - Cater-Steel, Aileen 1954- (Premier reference source, 2009)
"This book provides an in-depth view into the critical contribution of IT service management to IT governance, and the strategic and tactical value provided by effective service management" - Provided by publisher